Revealing the Salience of Hashtags on the @pulauplastik Account Through Ecolinguistics Lens - Made Sani Damayanthi Muliawan; I Wayan Simpen; Made Sri Satyawati; I Nyoman Suparwa (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
This study investigates the salience of hashtags used on the @pulauplastik Instagram account through the lens of ecolinguistics. Captions and photos were used to collect data from the @pulauplastik Instagram account. Data was analyzed using ecolinguistic theory of salience. Through an ecolinguistic perspective, this research reveals the importance of using hashtags in campaigning for environmental preservation via Instagram social media, especially the @pulsplastic account. The results of this research show that effective use of hashtags can increase the salience of environmental conservation issues, attract users' attention, and encourage active participation in conservation efforts. As such, this research provides a valuable contribution to environmental communications strategy, offering practical guidance for activists, policymakers, and communities in designing more effective campaigns in the digital era. Using salience or prominence in hashtags can show how language can play an important role in increasing awareness and participation of social media users on the issue of plastic pollution and environmental conservation. Keywords Environmental Hasthag, Salience, Ecolinguistic